2015
DOI: 10.17762/ijritcc2321-8169.1504141
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on Various Payment Options in Online Shopping

Abstract: Abstract:-E-commerce is increase rapidly in India in the form of online shopping. An IT firm Accel Partners has released some data's on online shopping in India. According to them Indian online shopping industry have a turnover of 700 crore Rs. by 2015 and around 30 lacs Indian shopper used online shopping. The main objective of this research is to study, especially what is the major option for payments in online shopping. There is several option of payment in online purchasing such as credit card, debit card,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Considering these factors, Punwatkar [27] found that when transmitting strong super structural loads to poorer soils, the Shell foundation may be a more cost-effective substitute than a plain foundation. Savings in concrete and reinforcing steel may be substantial when shell foundations are used in place of spread footings and rafts.…”
Section: Numerical Overview Researchesmentioning
confidence: 99%
“…Considering these factors, Punwatkar [27] found that when transmitting strong super structural loads to poorer soils, the Shell foundation may be a more cost-effective substitute than a plain foundation. Savings in concrete and reinforcing steel may be substantial when shell foundations are used in place of spread footings and rafts.…”
Section: Numerical Overview Researchesmentioning
confidence: 99%
“…The total sample sizes of 40 were collected through a questionnaire by using a convenient sampling method, the outcome of the study is the greatest number of users are happy with online shopping and mainly interested in buying online apparel. Chirag Parmar, (2015), The main objective of the research is to study, especially the major option for payments in online shopping. There are several payment options in online purchasing such as credit card, debit card, cash on delivery, EMI option, gift voucher or wallet Rs.…”
Section: Review Of Literaturementioning
confidence: 99%
“…This research develops a theoretical model of consumers" perceived security and perceived trust, including their roles in the use of digital payment system. A research article published by Chirag, namely "A Comparative Study on Various Payment Options in Online Shopping" (Parmar, 2015) presents before us various options that can be availed by the online shoppers while shopping digitally. The researcher has the objective of "To analyses and identified the various payment option of online shopping with people of different market and general public in Bikaner city" (Parmar, 2015,).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A research article published by Chirag, namely "A Comparative Study on Various Payment Options in Online Shopping" (Parmar, 2015) presents before us various options that can be availed by the online shoppers while shopping digitally. The researcher has the objective of "To analyses and identified the various payment option of online shopping with people of different market and general public in Bikaner city" (Parmar, 2015,). The researcher had come to the conclusion that the major users use the cash on delivery option and of 16 to 30 years age group.…”
Section: Literature Reviewmentioning
confidence: 99%